Study on the Seroprevalence of Cystic Echinococcosis and Toxocariasis in the Rural Population Referred to Reference Laboratory in Urmia, Northwest Iran - Fatemeh Ramzi; Rasool Jafari; Elham Yousefi (Journal of Parasitology Research)
Conclusion: Based on the results of the present study, both CE and toxocariasis are present in rural areas of Urmia District, which is alarming, because CE is a serious infection even with low prevalence. Toxocariasis, on the other hand, is considerably high in prevalence, showing the high risk of infection with Toxocara spp. in these areas.